Light-ion production and fission studies using the MEDLEY facility at TSL - S. Pomp (2018)
© Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence. The MEDLEY facility at the The Svedberg Laboratory (TSL) in Uppsala has successfully been used in several light-ion production and elastic scattering experiments at 96 MeV. The recent upgrade of the neutron beam facility at TSL now makes the energy range up to 175 MeV accessible. To match the higher energies MEDLEY has been equipped with larger CsI detectors and first tests runs have been performed. The research program at MEDLEY has been extended to include, e.g., studies of neutron-induced fission, especially angular distributions of the fission fragments, over a wide energy range. We present the current status of the facility and the planned research program.